1973
DOI: 10.1139/v73-191
|View full text |Cite
|
Sign up to set email alerts
|

The Reaction of CH3+ with D2

Abstract: The exchange reaction between CH3+ and D2 leading to CH2D+ and CHD2+ is shown to proceed through a collision complex in which the hydrogens and deuteriums become equivalent. The rate coefficient for reaction of CH3+ with D2 is 6.1 ± 0.1 × 10−10 cm3 molecule−1 s−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1973
1973
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…(J Am SocMass Spectrom 1994,5,282-291) M ass spectrometric studies on hydrogendeuterium (HID) exchange reactions in solution have been used for structure elucidation' [1,2]. Kinetic studies on isotopic methane-hydrogen and methane-deuterium systems have demonstrated the feasibility of HID exchanges in the gas phase [3][4][5]. Presumably, the reactant ions involved for the exchange reactions include Ht, D;, CHt, CD;, CHi, CDt, CHt, and CD~.…”
mentioning
confidence: 99%
“…(J Am SocMass Spectrom 1994,5,282-291) M ass spectrometric studies on hydrogendeuterium (HID) exchange reactions in solution have been used for structure elucidation' [1,2]. Kinetic studies on isotopic methane-hydrogen and methane-deuterium systems have demonstrated the feasibility of HID exchanges in the gas phase [3][4][5]. Presumably, the reactant ions involved for the exchange reactions include Ht, D;, CHt, CD;, CHi, CDt, CHt, and CD~.…”
mentioning
confidence: 99%
“…nziq 33 and, at higher pressures, ~q 32 in the HZ CI of HC02C2D5 suggests that there is a slob exchange of the C2D5+ ion with HZ, similar to the known exchange reaction of CH3-with DZ (9). The m 'q 28 product (C2H4+) is -6-87, of the total ionization at low H2 pressures and decreases rapidly in importance with increasing H2 pressure.…”
Section: Chet??iccil Ionizntio~z Of' E R L~~l Forr?~c~tementioning
confidence: 81%
“…The addition of phenylium ions to hydrogen molecules has some precedent in the formation of a collision complex between methyl cations CH3+ and D2 that is sufficiently long lived for the hydrogens and deuteriums to become equivalent. 21 In our experiments CeHs4" ions are produced both by electron impact and by dehalogenation of halobenzenes by gaseous Bronsted acids. The reactivity of CeHs4 does not seem to depend on its mode of formation, suggesting that the same electronic state is formed in both processes, and with similar internal energies.…”
Section: Discussionmentioning
confidence: 94%